Dual-functional aniline-assisted wet-chemical synthesis of bismuth telluride nanoplatelets and their thermoelectric performance. (17th May 2017) - Li, Changcun; Kong, Fangfang; Liu, Congcong; Liu, Huixuan; Hu, Yongjing; Wang, Tongzhou; Xu, Jingkun; Jiang, Fengxing
Abstract: The wet-chemical approach is of great significance for the synthesis of two-dimensional (2D) bismuth telluride nanoplatelets as a potential thermoelectric (TE) material. Herein, we proposed a simple and effective solution method with the assistance of aniline for the fabrication of bismuth telluride nanoplatelets at a low temperature of 100 °C. The choice of aniline with its dual function avoided the simultaneous use of a capping regent and a toxic reductant. The as-synthesized nanoplatelets have a large size of more than 900 × 500 nm 2 and a small thickness of 15.4 nm. The growth of bismuth telluride nanoplatelets are related to the Bi/Te ratio of precursors indicating that a larger content of the Bi precursor is more conducive to the formation of 2D nanoplatelets. The bismuth telluride nanoplatelets pressed into a pellet show a smaller electrical resistivity (∼6.5 × 10 −3 Ω · m) and a larger Seebeck coefficient (−135 μ V K −1 ), as well as a lower thermal conductivity (0.27 W m −1 K −1 ) than those of nanoparticles. The next goal is to further reduce the electrical resistivity and optimize the TE performance by disposing of the residual reactant of aniline adsorbed on the surface of the nanoplatelets.